Identification of genes conferring resistance to furan in Caenorhabditis elegans - Cai, Ning (2009)
Furan is a heterocyclic organic compound which is a liver carcinogen in mice and rats, associated with short-term liver toxicity and hepatic pathology; however, the mechanism of induction of these acute effects by furan is unknown. The aim of this study was to examine the toxicity of furan in C. elegans and identify the genes in mutagenised C. elegans responsible for resistance to furan, with the aim of identifying a mechanism of action of furan as a toxin in C. elegans. It would then be possible to test if the mechanism of acute toxicity of furan in C. elegans and mammals is conserved. The growth of L1 larvae and brood size of N2 C. elegans were studied, and the effect of furan on these endpoints was measured by constructing full dose-response curves (n>3 for each point). Furan was toxic in both assays (EC50~2.7mM) and 30mM furan killed all offspring. N2worms (P0) were mutagenised with Ethyl Methane Sulphonate (EMS), and F1 generation worms at L4 stage were incubated with 30mM furan for three days. No offspring were obtained from non-mutagenised worms, but several lines of furan-resistant worms were obtained from mutagenised worms. Resistance to furan was shown to segregate as a recessive trait in crosses with N2 worms, and five independent resistant lines were shown to form three complementation groups. Both lines from one complementation group showed a high incidence of males (HIM) phenotype. The approximate location of this furan resistant gene was mapped on the left arm of chromosome V for resistant line 2. Future work will involve the fine mapping and identification of furan resistance genes.